Didactic strategy with math to develop utility models in times of covid-19 in architecture - Jaimes-Reátegui, Sumaya (2021)
A didactic strategy is presented, with a problem solving approach, through mathematical modeling to the design and implementation of a product (utility model) to prevent the spread of COVID-19. The above, was realized in the topic of mathematics III, during the 2020-I semester in the Professional Career of Architecture of the National University Hermilio Valdizán de Huánuco-Peru. The research was realized by a quantitative approach, descriptive level and non-experimental design. This strategy consisted of 5 phases: phase 1: formulation of the context problem to prevent the spread of COVID-19, with a utility model using quadratic or curved surfaces; phase 2: theoretical framework and objectives; phase 3: mathematical modeling; phase 4: drawing up the utility model plans; phase 5: 3D utility model. The evaluation of the strategy was carried out through rubrics of: teacher evaluation, self-evaluation, co-evaluation among students and hetero-evaluation of experts. We concluded that, with the application of the strategy, most of the students achieved a level of performance higher than expected (decisive) in obtaining of the utility model, allowing to the students relate mathematic with real life problem, with complex thinking, creativity and applying knowledge of the Architecture bachelor.